PENGARUH PRICE EARNING (PER), EARNING PER SHARE (EPS), DEBT TO EQUITY RATIO (DER) TERHADAP HARGA SAHAM - Iwan Firdaus; Ana Nasywa Kasmir (Universitas Prof. Dr. Moestopo (Beragama), 2021)
This research was conducted to examine the effect of Price Earning Ratio (PER), Earning Per Share (EPS), and Debt to Equity Ratio (DER) to stock prices. The object for this research is property and real estate industries listed on the Indonesia Stock Exchange in the period 2012-2016. This research was conducted using quantitative menthod with total 35 sample of research were determined by purposive sampling method. Method of hypothesis testing using t-test. This research use Price Earning Ratio (X1), Earning Per Share (X2), Debt to Equity Ratio (X3) as independent variable and Stock Price as dependent variable. The results of this research are Price Earning Ratio and Earning Per Share positive and has significant effect to stock prices, whlile the Debt to Equity Ratio positive and has no significant effect to stock prices.